2008 Winter Simulation Conference 2008
DOI: 10.1109/wsc.2008.4736284
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based sustainable manufacturing system design

Abstract: Manufacturing simulation and digital engineering tools and procedures have had a positive impact on the manufacturing industry. However, to design a sustainable manufacturing system, a multitude of system dimensions must be jointly optimized. This paper proposes an integrated simulation tool helping to maximize production efficiency and balance environmental constraints already in the system design phase. Lean manufacturing, identification and elimination of waste and production losses, and environmental consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(88 citation statements)
references
References 8 publications
0
85
0
3
Order By: Relevance
“…The increasing laws and regulations, coupled with the recognition that developing more ecofriendly manufacturing operations is "the right thing to do" have put sustainability at or near the top of most manufacturing firms' agendas and enhanced the firm performance (Heilala et al, 2008). In line with this, Smith and Perks (2010) suggested that manufacturing firm can improve its competitiveness and firm performance through improvements in environmental performance as a result of compliance with environmental policy and regulation, at the same time address the environmental concern of customers and reduce the environmental impact of their products and services.…”
Section: Policy and Regulation And Firm Performancementioning
confidence: 99%
“…The increasing laws and regulations, coupled with the recognition that developing more ecofriendly manufacturing operations is "the right thing to do" have put sustainability at or near the top of most manufacturing firms' agendas and enhanced the firm performance (Heilala et al, 2008). In line with this, Smith and Perks (2010) suggested that manufacturing firm can improve its competitiveness and firm performance through improvements in environmental performance as a result of compliance with environmental policy and regulation, at the same time address the environmental concern of customers and reduce the environmental impact of their products and services.…”
Section: Policy and Regulation And Firm Performancementioning
confidence: 99%
“…Recreation models produced by help of separate concepts in event simulation [13] help envisage the whole manufacturing system and examine possible environmental influences on the up-to-date system design bring about. This enables both systems designers and engineers to remake the system in order to increase its level of efficiency.…”
Section: Technology Challengesmentioning
confidence: 99%
“…An example of such a combination is discrete event simulation (DES) and LCA. Various different examples of successful LCA-DES combinations have been carried out and presented before [29][30][31][32].…”
Section: Lca and Fisheriesmentioning
confidence: 99%